Analysis of radar satellite images for terrains characterization in the Colombian countryside (2022)
Study of Colombian terrains, which are part of PDET municipalities and projects of Colombia Sostenible, through radar images from the Sentinel-1 satellite of the European Space Agency and fieldwork data from the 2014 National Agricultural Census, to identify vegetation levels and bodies of water in them.